(untitled) - White II, Nathaniel A. (Philadelphia, 1998)
Virginia Polytechnic Institute and State Univ., Leesburg. Provides current information from research, journals, and electronic discussions on the Internet. For surgeons, practitioners, students, and residents. Extensively referenced. Halftone illustrations. Trim size: 11 x 9 inches. Previous edition was not cited.
Keywords: Horses,Horses,Loài ngựa,Loài ngựa; Surgery,Diseases,Phẫu thuật,Bệnh tật